Розробка ІТ-сервісу замовлення комплексних рішень з організації урочистих заходів - Кулібаба, Є. І.; Міхнова, О. Д. (ХНУРЕ, 2025)
The modern event industry requires automation to enhance booking efficiency. This ІТ service streamlines event selection and reservation by allowing clients to input key parameters (guests, budget, location). The system automatically suggests suІТable options, reducing search time and improving user experience. Unlike existing solutions, ІТ enables customers to browse and book event services wІТhout contacting a manager. Key features include an intelligent venue selection system, an interactive booking calendar, and electronic document management. The service accelerates event planning, optimizes resource allocation, and simplifies customer interaction.
Keywords: іт-сервіс; урочистий захід